Edukasi Ramuan Herbal untuk Mengatasi Gejala Ispa pada Kelompok Asuhan Mandiri Kesehatan Tradisional di Kelurahan Teluk Tiram Banjarmasin - Fitri Puspitasari; Deni Setiawan; Riswandayani Savitri; Samsul Hadi; Okta Mutia Sari; Nurul Mardiati (Universitas Kristen Indonesia Toraja, 2024)
Air pollution has a broad impact on the people of South Kalimantan and causes the incidence of ISPA. TOGA utilization is still low due to a lack of public knowledge about plant types and their uses. The aim of this activity is to increase the knowledge of traditional independent health care groups. This activity was held on Monday, October 9 2023 at 13.30 – 15.30 WITA which was attended by 10 cadres. Activities are carried out using the lecture method and using leaflets. The leaflet material contains the definition of ISPA, general instructions regarding the processing of natural ingredients as potions, the composition of potions for coughs and colds, sore throats, shortness of breath and potions to increase body endurance. Evaluation of activities is carried out using pretest and posttest methods. The activity went well and succeeded in increasing the knowledge of the cadres.